Clinical features, treatment, and outcome of isotretinoin-associated sacroiliitis - Shaoli Zhao; Wei Sun; Liping Peng; Chunjiang Wang (Arthritis Research & Therapy)
Abstract Background Sacroiliitis is a rare adverse reaction of isotretinoin. However, the data on the clinical features, treatment and outcomes of isotretinoin-associated sacroiliitis are limited. This study was conducted to explore the clinical characteristics of isotretinoin-associated sacroiliitis, providing a basis for diagnosis and treatment. Methods The author retrieved clinical reports of isotretinoin-associated sacroiliitis from the database for a retrospective analysis up to March 31, 2025. Results A total of 67 patients were included, with a median age of 21 years (range 14, 44). Fifty-six (83.6%) of the patients were from Turkey. The median time of sacroiliitis was 2.5 months (range 0.4, 24) after isotretinoin administration. Low back pain (70.1%) and hip pain (44.8%) are the main symptoms of patients with sacroiliitis. Magnetic resonance imaging (MRI) mainly showed sacroiliitis (73.1%) and bone marrow edema (34.3%). After discontinuation of isotretinoin and treatment with non-steroidal anti-inflammatory drugs (NSAIDs) and biologics, the patient’s symptoms and MRI improved. Conclusion Patients treated with isotretinoin who experience low back pain should consider the possibility of sacroiliitis. MRI is a useful tool for the diagnosis of sacroiliitis. The cessation of isotretinoin therapy, coupled with the administration of NSAIDs, can effectively alleviate the symptoms experienced by patients.